Promoting cooperation in South Asia : an agenda for the 13th SAARC Summit - Sobhan, Rehman; South Asia Centre for Policy Studies; Centre for Policy Dialogue (Bangladesh) (Dhaka : The University Press, 2004)
Papers presented at a conference held in 2004 in Sussex, England.
"South Asia Centre for Policy Studies, Centre for Policy Dialogue."
Includes bibliographical references.
Keywords: South Asia -- Economic policy -- International cooperation -- Congresses; South Asia -- Commerce -- International cooperation -- Congresses; Social planning -- South Asia -- International cooperation -- Congresses